Application of Carbon-Based Nanomaterials in Acid-Base Sensors. Issue 1 (4th May 2021) - Du, Qifei; Sha, Lin
Abstract: At present, long-term flight of carrier-based aircraft and other naval aviation equipment in high-salt, high-humidity environments will be subject to various environmental corrosion. The traditional means of monitoring aircraft corrosion is to seal water and prevent periodic inspections. The two monitoring methods are inefficient, and it is not easy to find the corrosion condition in the early stage of corrosion. When the corrosion really occurs, it will seriously threaten the safe flight of the aircraft and the safety of the pilot. Therefore, there is a need to develop an on-line monitoring sensor device for aircraft corrosion conditions to carry out real-time monitoring of aircraft acid-base corrosion (pH) conditions in high-salt, high-humidity marine environments. This paper mainly studies the application of carbon-based nanomaterials in acid-base sensors. In this paper, the acid-base sensor potential values at the same pH value are changed back and forth. In the initial state, the acid-base sensor potential values corresponding to pH = 3 are 385, 386, 379, and 392 mV, respectively. After 1500 s, the potential values of the acid-base sensor were 384, 383, 377, and 390 mV, and the three-phase hysteresis potential of the acid-base sensor was 1, 3, 2, and 2 mV, indicating that the acid-base sensor produced a small hysteresis potential. However, the amount of sensor drift is within a controllable range, and the response time of the acid-base sensor is relatively short regardless of the solution with different pH values added dropwise from acid to alkali or from alkali to acid. Therefore, the acid-base sensor has good hysteresis and recyclability.